A “model” as a model: Fabio Mancini European School Project [Article in English and Italian] • [Un “modello” come modello: Fabio Mancini European School Project] [Article in English and Italian] - Mancini, Fabio; Chinellato, Iolanda; Polizzi, Concetta; Marseglia, Gian Luigi; Fanos, Vassilios (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2024)
ENGLISH TEXT Introduction and state of the art: Adolescence is an age characterized – as is well known – by sudden changes at the physical and psycho-cognitive levels, in which adolescents go through complex phases in which affective, emotional and especially social-relational difficulties are intertwined. The most recent orientations in developmental psychology, however, have shifted the focus of the approach to this fundamental phase of development, hitherto framed in the “critical” perspective of difficulties and stress to overcome. By adopting the paradigm of positive psychology, attention can be focused on good practices functional to the promotion of individual well-being, through training that starts from the acquisition of greater self-awareness and the potential to be implemented in order to achieve one’s own well-being (psychological well-being) and, therefore, “happiness”, a term used here net of the legitimate questions that such a complex state of mind poses in order to its very precise definition. Even in the ministerial guidelines of education in several European countries, including Italy, there is now a reversal of the previous promotion of a digital school and e-learning model, pointing to a general reduction in the use of electronic devices (PCs, tablets and cell phones) for educational purposes, in favor of more traditional forms and environments of learning, centered on cooperative learning and social learning. Project goals: The purpose of the project is to monitor and evaluate the psychological well-being of students, as well as the usefulness of the impact, for this purpose, of the mediation of a communicative model based on direct relationship with a public figure in the school context. Regarding the first point, it is intended to administer, adapting it appropriately, the Oxford Happiness Questionnaire (OHQ), an instrument used to detect the degree of happiness and subjective well-being of individuals. In the implementation of monitoring and of useful interventions in the pursuit of adolescents’ well-being within the educational context, it is believed that a key and innovative role can be played by the active participation in the project of a reference figure for young people, such as a person from outside the school world, with his own successful human and professional educational experience, who offers young people a positive model of dialogue and direct confrontation. The goal is to complement and enrich the socio-affective interaction with adolescents with concrete and direct human input, not mediated by social media. In this direction, the testimony of one of the most sought-after and established international supermodels, known as a “beauty ambassador with a human side,” engaged in volunteer work, philanthropic activities and collaborative projects in various school contexts and in pediatric long-term care wards, can help foster dialogue with adolescents and the exchange of experiences, expectations and ideas useful in overcoming those critical factors that hinder the well-being and serenity of adolescents, especially in contexts of social marginality and educational poverty. Type of intervention, materials and methods: The beneficiaries of the project are preadolescents and adolescents, and the planned interventions are implemented within schools, as places not only of curricular education, but understood as primary places of community life, socialization and protection of the health and mental and physical well-being of adolescents. The project involves the administration of the OHQ appropriately adapted to students in Italian schools participating in the Adolescent Well-Being School Project. The objective of this questionnaire is to measure happiness in general, that is, psychological well-being. If the OHQ can now boast of an effective use proven by a large number of studies in numerous countries, including non-European ones, the novelty of the present proposal consists mainly in the innovation of the administration context, through a different communicative model, which, playing intentionally with the term that gives the project its title, can also be represented by a supermodel in the role of mediator and facilitator of some phases of the action itself. This choice, as well as being original, is deliberately antithetical to the current trend, which privileges, especially in operations of this type and, more generally, in the context of the daily lives of adolescents, virtual and media relationships, with all the risks of socio-relational deprivation that have already been mentioned and which are, moreover, before everyone’s eyes. The choice therefore falls on a mediating figure who can at the same time offer a concrete and evident testimony to a state of well-being that is also physical, insofar as it comes from a healthy lifestyle, in which, of course, care for nutrition and regular exercise practiced without excesses are included. Expected results: The ultimate goal is the diffusion and dissemination, among adolescents, of good practices of real and direct, healthy and constructive relationships, both in the peer relationship and in the relationship with family, educational institutions and society. The perspective is to provide support for the development and maturation, as early as adolescence, of skills and attitudes for the construction and maintenance of ongoing individual well-being, a perspective where the individual and autonomous propensity for lifelong learning is also complemented by the fundamental one for lifelong well-being. ITALIAN TEXT Introduzione e stato dell’arte: L’adolescenza è un’età caratterizzata – come è noto – da repentini cambiamenti a livello fisico e psico-cognitivo, in cui i ragazzi attraversano fasi complesse nelle quali s’intrecciano difficoltà affettive, emotive e soprattutto socio-relazionali. I più recenti orientamenti della psicologia dell’età evolutiva hanno però spostato il focus dell’approccio a questa fase fondamentale dello sviluppo, finora inquadrata nella prospettiva “critica” delle difficoltà e dello stress da superare. Adottando il paradigma della positive psychology, l’attenzione può essere puntata su buone prassi funzionali alla promozione del benessere individuale, attraverso un training che parte dall’acquisizione di una maggiore consapevolezza di sé e delle potenzialità da attuare al fine del raggiungimento del proprio benessere (psychological well-being) e, quindi, della “felicità”, termine adoperato qui al netto delle legittime questioni che uno stato dell’animo così complesso pone in ordine a una sua definizione ben precisa. Anche negli orientamenti ministeriali dell’istruzione in diversi paesi europei, compresa l’Italia, si assiste oggi a un’inversione di tendenza rispetto alla precedente promozione di un modello di scuola digitale e di e-learning, puntando a una riduzione generale dell’impiego dei dispositivi elettronici (pc, tablet e cellulari) a fini didattici, a favore di forme e ambienti di apprendimento più tradizionali, incentrati sul cooperative learning e l’apprendimento sociale. Obiettivi del progetto: Scopo del progetto è monitorare e valutare il benessere psicologico degli studenti, nonché l’utilità dell’impatto, a tal fine, della mediazione di un modello comunicativo fondato sulla relazione diretta con un personaggio pubblico nel contesto scolastico. Per quanto concerne il primo punto, s’intende somministrare, adattandolo opportunamente, l’Oxford Happiness Questionnaire (OHQ), strumento utilizzato per rilevare il grado di felicità e benessere soggettivo degli individui. Nell’attuazione del monitoraggio e di interventi utili al perseguimento del benessere degli adolescenti nell’ambito del contesto formativo, si ritiene che possa svolgere un ruolo chiave e innovativo la partecipazione attiva al progetto di una figura di riferimento per i giovani, quale può considerarsi un soggetto esterno al mondo della scuola, con una propria esperienza formativa umana e professionale di successo, che offra ai ragazzi un modello positivo di dialogo e confronto diretto. L’obiettivo è quello di integrare e arricchire l’interazione socioaffettiva con gli adolescenti di un apporto umano concreto e diretto, non mediato dai social media. In tale direzione, la testimonianza di un top model fra i più ricercati e affermati a livello internazionale, noto come “beauty ambassador dal lato umano”, impegnato nell’ambito del volontariato, in attività filantropiche e in progetti di collaborazione in diversi contesti scolastici e nei reparti pediatrici di lungodegenza, può contribuire a favorire il dialogo con gli adolescenti e lo scambio di esperienze, aspettative e idee utili al superamento di quei fattori di criticità che ostano al benessere e alla serenità degli adolescenti, soprattutto in contesti di marginalità sociale e di povertà educativa. Tipologia d’intervento, materiali e metodi: I soggetti beneficiari del progetto sono i preadolescenti e gli adolescenti, e gli interventi previsti sono attuati all’interno delle scuole, quali presidi non solo della formazione curricolare, ma intese come luoghi primari di vita comunitaria, di socializzazione e di tutela della salute e del benessere psico-fisico degli adolescenti. Il progetto prevede la somministrazione dell’OHQ opportunamente adattato agli studenti delle scuole italiane che aderiscono all’Adolescent Well-Being School Project. L’obiettivo di questo questionario è misurare la felicità in generale, cioè il benessere psicologico. Se l’OHQ può vantare ormai un impiego efficace e comprovato da una nutrita serie di studi in numerosi paesi anche extra-europei, la novità della presente proposta consiste principalmente nell’innovazione del contesto di somministrazione, attraverso un diverso modello comunicativo, che, giocando volutamente con il termine che dà il titolo al progetto, può essere rappresentato anche da un top model in veste di mediatore e facilitatore di alcune fasi dell’azione stessa. Tale scelta, oltre che originale, è volutamente antitetica all’attuale tendenza, che privilegia, soprattutto in operazioni di questo tipo e, più in generale, nel contesto della vita quotidiana degli adolescenti, le relazioni virtuali e mediatiche, con tutti i rischi di deprivazioni socio-relazionali cui si è già accennato e che sono, del resto, sotto gli occhi di tutti. La scelta ricade perciò su una figura di mediazione che possa al tempo stesso offrire una testimonianza concreta ed evidente di uno stato di benessere che è anche fisico, in quanto riveniente da un regime di vita sano, in cui naturalmente rientrano la cura dell’alimentazione e un esercizio fisico regolare e praticato senza eccessi. Risultati attesi: L’obiettivo finale è la diffusione e disseminazione, fra gli adolescenti, di buone prassi di relazioni reali e dirette, sane e costruttive, sia nel rapporto tra pari sia nel rapporto con la famiglia, le istituzioni formative e la società. La prospettiva è quella di fornire un supporto allo sviluppo e alla maturazione, sin dall’adolescenza, di capacità e attitudini alla costruzione e al mantenimento di un benessere individuale costante, una prospettiva che alla propensione individuale e autonoma al lifelong learning affianchi anche quella imprescindibile al lifelong well-being.